Taxonomic catalogue of the Spionidae (Annelida: Polychaeta) of the Grand Caribbean - Delgado-Blas, Victor Hugo; Salazar-Silva, Patricia (Zootaxa, 2011)
The aim of this study was to provide a revised taxonomic catalogue of Spionidae species recorded from the Grand Caribbean. The names included were compiled from the checklists of Salazar-Vallejo (1996) and Perkins and Savage (1975). Names were revised and updated based on recent revisions. For each species, the original name is included together with current and previous names under which it has been recorded; all with associated citations. The type locality of each species, museum or institution where the type materials are deposited, and comments on systematics and geographic distributions are also included. The catalogue lists 66 species in 24 genera and at the end a list of species with questionable distribution in the Grand Caribbean is included.